Building Beasties: Disability, Imperialism, and Violence in William Golding’s Lord of the Flies (1954) - Holdsworth, Dylan (The Government of Disability in Dystopian Children’s Texts, 2024)
By the end of World War II Britain was faced with substantial challenges. There was considerable economic strain with the cost of rebuilding, a large amount of temporarily and permanently disabled and traumatised civilians, soldiers, and medical personnel, as well as British involvement in 11 geopolitical events (including the Northern Campaign from 1942 to 1944 by the Irish Republican Army) in the decade after the end of World War II. These factors signalled the financial and human costs of war for Britain and contributed to the global weakening of British imperial authority and its ability to suppress and resolve geopolitical tensions, movements, conflicts, and shifts. The British Empire found itself confronted by uprisings and wars for independence (the Northern Campaign; Indonesian National Revolution from 1945 to 1949; the 1951-1952 Anglo-Egyptian War; the Mau Mau Uprising in British Kenya from 1952 to 1960; and the beginning of both the Jebel Akhdar War in Oman from 1954 to 1959 and the Cyprus Emergency from 1955 to 1959) as well as attempting to stem the expansion of Communism across Europe and Asia (the Greek Civil War from 1944 to 1948; Operation Masterdom in Vietnam from 1945 to 1946; the Corfu Channel Incident with the People’s Socialist Republic of Albania from 1946 to 1948; the Malayan Emergency from 1948 to 1960; and the Korean War from 1950 to 1953). Britain’s involvement in such extensive conflicts demonstrates the implicit anxiety regarding its place in the post-War world. However, as Andrew Hammond summarises it, "Just as Britain helped to shape the course of global events, so those events shaped aspects of British life, from the Welfare State and the peace movement, through nuclearization, decolonization, unionism, and recession, to Labour’s retreat from socialism and the quandaries of post-imperial nationhood" (2011:663). Although Britain was exercising its might internationally, there were also several major political shifts which affected the lives of people at home.